A személyiségi jogok védelme a reklámtörvény tükrében - Kiss, Tibor (Debreceni Jogi Műhely, 2006)
There is a significant inconsistency within the domain of enforcement of inherent rights in the Hungarian regulation. The protection of the inherent rights is based on the section 75 of Act IV of 1959 (hereinafter: „Civil Code”), which provides that inherent rights shall be observed by everyone and inherent rights are protected by law. The lack of consistency can be led back to the difference between the provisions of the Civil Code and Act LVIII of 1997 on Business Advertising Activity. Under Section 85 of the Civil Code inherent rights may only be enforced in person. There are two exceptions to the above rule laid down in the Civil Code: The legal representative of an incompetent person, or the relative or conservator of a missing person whose whereabouts are unknown shall be entitled to proceed in the protection of that person’s inherent rights. In the case of impairment to the memory of a deceased person, the relative and/or the person having been named as the heir apparent in the will of the deceased shall be entitled to file a court action. If conduct causing defamation to a deceased person (former legal person) infringes upon the public interest, the public prosecutor shall also be entitled to enforce this inherent right. The Act on Business Advertising Activity provides for several general advertising prohibitions and restrictions. Under Section 4 of this act advertising may not be published if it infringes personal rights, respect for the deceased or rights related to the protection of personal data. Under Section 16 of this act advertising control proceedings may be initiated upon request or ex officio. Based on the regulation of the Act on Business Advertising Activity advertising control proceedings may be requested by any person whose rights or rightful interests, or legal status is injured by violation of any provisions relating to commercial advertising activity. If the aggrieved consumer cannot be identified, or if enforcement of the claims is inappropriate considering the number of consumers injured, administrative agencies or non-governmental organizations providing for consumer interests shall also be entitled to initiate proceedings. When the regulations of the Civil Code on enforcement of inherent rights are compared with that of the Act on Business Advertising Activity, it can be established that provisions of the latter act are not in compliance with the provisions of the Civil Code. On the basis of the decision No. 1270/B/1997 of the Hungarian Constitutional Court, the inconsistency is not significant, the different regulatory of the mentioned acts is not unconstitutional. I take the view that in order to achieve consistent regulation the Act on Business Advertising Activity should be modified by prohibiting the advertising control proceedings initiated ex officio in relation to the advertisings which infringe personal rights.